2013
DOI: 10.1128/jb.00397-13
|View full text |Cite
|
Sign up to set email alerts
|

Function of a Glutamine Synthetase-Like Protein in Bacterial Aniline Oxidation via γ-Glutamylanilide

Abstract: Acinetobacter sp. strain YAA has five genes (atdA1 to atdA5) involved in aniline oxidation as a part of the aniline degradation gene cluster. From sequence analysis, the five genes were expected to encode a glutamine synthetase (GS)-like protein (AtdA1), a glutamine amidotransferase-like protein (AtdA2), and an aromatic compound dioxygenase (AtdA3, AtdA4, and AtdA5) (M. Takeo, T. Fujii, and Y. Maeda, J. Ferment. Bioeng. 85:17-24, 1998). A recombinant Pseudomonas strain harboring these five genes quantitatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 57 publications
(81 reference statements)
0
40
0
Order By: Relevance
“…To test its function, the plasmid pBBRQR harbouring adoQTA1A2BR was introduced into Pseudomonas putida KT2440-DcatA (in which both catechol dioxygenase genes were deleted) (Takeo et al, 2013). Gas chromatographymass spectrometry (GC-MS) analysis showed that 4-IA was transformed into 4-IPC (Supporting Information Fig.…”
Section: Genome Features Of Three Ipu-mineralizing Sphingomonads and mentioning
confidence: 99%
“…To test its function, the plasmid pBBRQR harbouring adoQTA1A2BR was introduced into Pseudomonas putida KT2440-DcatA (in which both catechol dioxygenase genes were deleted) (Takeo et al, 2013). Gas chromatographymass spectrometry (GC-MS) analysis showed that 4-IA was transformed into 4-IPC (Supporting Information Fig.…”
Section: Genome Features Of Three Ipu-mineralizing Sphingomonads and mentioning
confidence: 99%
“…This enzyme is capable of catalyzing the production of γ-glutamylaniline in an ATP-dependent manner (Fig. 6a) [80]. AtdA1 was also found to act on aniline derivatives such as 2-, 3-, and 4-chloroaniline and 2-, 3-, and 4-methylaniline.…”
Section: Introductionmentioning
confidence: 99%
“…Through sequence analysis, one gene cluster containing 14 catabolic genes for complete aniline degradation was identified. The first six genes (dcaQTA1A2BR) encode a Lglutamate-based oxidative deamination pathway which transforms aniline to catechol (Takeo et al 2013). The rest of the eight genes in the cluster encode the lower pathway featured by a 2,3-dioxygenase and other enzymes capable of converting 2-hydroxy-muconaesemialdehyde into TCA intermediates (Fig.…”
Section: Biodegradation Of Aromatic Compoundsmentioning
confidence: 99%